Single‐Center Evaluation of the Myval Balloon‐Expandable Transcatheter Heart Valve: A Follow‐Up Study: A Retrospective Cohort Study - Mohammadreza Baay; Ata Firouzi; MohammadHossein MozafaryBazargany; Amir Azimi; Armin Elahifar; Mohammad Javad Alemzadeh‐Ansari; Zahra Hosseini; Seifollah Abdi; Amineh Safairad; Peyman Bashghareh; Ehsan Khalilipur (Health Science Reports)
ABSTRACT Background and Aims Our objective is to report our single‐center experience with the novel balloon‐expandable Myval Transcatheter Heart Valve (THV) system in Transcatheter Aortic Valve Replacement (TAVR) procedures. Methods We conducted a retrospective study on a cohort of consecutive patients who underwent TAVR utilizing Myval THV from September 2021 to August 2023 at a tertiary care cardiac center. We collected baseline characteristics, pre‐ and post‐procedural echocardiographic findings, procedural details, in‐hospital outcomes, VARC‐3 technical success, and complications. Additionally, patients were followed up for 3 months concerning their clinical outcomes. Results The study population comprised 92 TAVR patients with a mean age of 76.8 ± 7.3 years, 66.3% were male, and the mean STS score was 5.9 ± 3.2%. The most common valve sizes used were 24.5 mm (30.4%), 23 mm (26.1%), and 27.5 mm (17.4%). Pre‐dilation was performed in 32 cases (34.8%), achieving a 93.5% technical success rate. In‐hospital mortality occurred in three patients (3.3%), which included one annulus rupture. Permanent pacemaker implantation was required in six patients (6.5%). Three patients (3.3%) exhibited 3+ paravalvular leakage demonstrated by angiography. The New York Heart Association (NYHA) functional class showed significant improvement from baseline to discharge (p < 0.0001). At the 3‐month follow‐up, five patients encountered mortality (5.4), and three experienced an episode of stroke or transient ischemic attack (3.2%). Two other patients were hospitalized due to cardiovascular events during the 3‐month follow‐up. Conclusion The Myval THV shows a favorable safety and efficacy profile in TAVR, with low mortality and complications at 3 months.